Aplicación Whatsapp E Inteligencia Interpersonal en los Estudiantes de la Carrera Psicología Educativa - Salinas Ponce, Jessenia Fernanda (2018)
The present research addressed the topic “WHATSAPP APPLOCATION AND INTERPERSONAL INTELLEGENCE AT THE STUDENTS OF THE EDUCATIONAL PSYCHOLOGY MAJOR-UNACH, RIOBAMABA, OCTOBER 2017-MARCH 2018”; it is a very important issue since we consider that thanks to the new technological eras our society is changing, but nobody trains us or guides us about the consequences that the exaggerated use or dependence of them implies, and for this reason we have chosen the target population study, among the students of the Educational Psychology major, with a sample of 251 people. The proposal was planned in order to know what is the usage level of the WhatsApp application through a survey and to identify the level of Interpersonal Intelligence that students have, the data was collected by using the Emotional Intelligence scale Daniel Goleman modified by Weisinger H, selecting the question based on the need of the project with the data obtained correlation was made between the two variables. The methodology for the study was qualitative approach; the non-experimental design; the types of research; descriptive, correlational, exploratory; for transverse time; by place, field and bibliographic, to stablish as conclusion, as much as you use this application, the less capacity for developing Interpersonal Intelligence and vice versa.